The Influence of Zn and Ca Addition on the Microstructure, Mechanical Properties, Cytocompatibility, and Electrochemical Behavior of WE43 Alloy Intended for Orthopedic Applications - Mircea Cătălin Ivănescu; Corneliu Munteanu; Ramona Cimpoeșu; Maria Daniela Vlad; Bogdan Istrate; Fabian Cezar Lupu; Eusebiu Viorel Șindilar; Alexandru Vlasa; Cristinel Ionel Stan; Maria Larisa Ivănescu; Georgeta Zegan (Medicina)
Background and Objectives: Magnesium (Mg)-based materials, such as the WE43 alloy, show potential in biomedical applications owing to their advantageous mechanical properties and biodegradability; however, their quick corrosion rate and hydrogen release restrict their general clinical utilization. This study aimed to develop a novel Mg-Zn-Ca alloy system based on WE43 alloy, evaluating the influence of Zn and Ca additions on microstructure, mechanical properties, cytocompatibility, and electrochemical behavior for potential use in biodegradable orthopedic applications. Materials and Methods: The WE43-Zn-Ca alloy system was developed by alloying standard WE43 (Mg–Y–Zr–RE) with 1.5% Zn and Ca concentrations of 0.2% (WE43_0.2Ca alloy) and 0.3% (WE43_0.3Ca alloy). Microstructural analysis was performed utilizing scanning electron microscopy (SEM) in conjunction with energy-dispersive X-ray spectroscopy (EDS), while the chemical composition was validated through optical emission spectroscopy and X-ray diffraction (XRD). Mechanical properties were assessed through tribological tests. Electrochemical corrosion behavior was evaluated using potentiodynamic polarization in a 3.5% NaCl solution. Cytocompatibility was assessed in vitro on MG63 cells using cell viability assays (MTT). Results: Alloys WE43_0.2Ca and WE43_0.3Ca exhibited refined, homogeneous microstructures with grain sizes between 70 and 100 µm, without significant structural defects. Mechanical testing indicated reduced stiffness and an elastic modulus similar to human bone (19.2–20.3 GPa), lowering the risk of stress shielding. Cytocompatibility tests confirmed non-cytotoxic behavior for alloys WE43_0.2Ca and WE43_0.3Ca, with increased cell viability and unaffected cellular morphology. Conclusions: The study validates the potential of Mg-Zn-Ca alloys (especially WE43_0.3Ca) as biodegradable biomaterials for orthopedic implants due to their favorable combination of mechanical properties, corrosion resistance, and cytocompatibility. The optimization of these alloys contributed to obtaining an improved microstructure with a reduced degradation rate and a non-cytotoxic in vitro outcome, which supports efficient bone tissue regeneration and its integration into the body for complex biomedical applications.